Has economics returned to being the 'dismal science'? The changing role of economic thought in German labour market reforms - Stephan Pühringer; Markus Griesser (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
As an immediate reaction to the recent financial crisis, it has been criticized that many economists are still acting as economic advisers for Ministries or the bureaucracy, although they have not been able to foresee the crisis . Academic economists still hold central positions in policy making; they influence decisions in economic expert panels or research departments in national and supranational organizations. Beside their role as policy advisors, economists also engage in public debates in a more narrow sense as technical economic experts as well as in a broader sense as "public intellectuals" in the process of the tra nsmission of economic knowledge in public (economic) policy discourses. In spite of the manifold critique about the state of economics in the aftermath of the crisis, an even increasing presence of economists and economic experts can be observed in the pu blic sphere during the last years . On the one hand this reflects the still dominant position of economics in the social sciences as well as the sometimes ignorant attitude of economists towards findings of other social sciences. On the other hand this pape r shows that the public debate on politico - economic issues among economists is dominated by a specific sub group of economists, tightly connected to an institutional network of "German neoliberalism". This group of "public economists" (i) is dominant in pub lic debates even after the financial crisis, (ii) reproduces the formative German economic imaginary of the Social Market Economy in a German neoliberal interpretation and (iii) has a good access to German economic policymaking, rooted in a long history of economic policy advice.
Keywords: 330; critical discourse analysis; political power of economic thought; labour market and social policy reforms; welfare state transformation